Theory of Fluid Instabilities in Partially Ionized Plasmas: An Overview - Soler, Roberto; Ballester, José Luis (Frontiers in Astronomy and Space Sciences, 2022)
Partially ionized plasmas (PIP) are essential constituents of many astrophysical environments, including the solar atmosphere, the interstellar medium, molecular clouds, accretion disks, planet ionospheres, cometary tails, etc., where the ionization degree may vary from very weak ionization to almost full ionization. The dynamics of PIP is heavily affected by the interactions between the various charged and neutral species that compose the plasma. It has been shown that partial ionization effects influence the triggering and development of fluid instabilities as, e.g., Kelvin-Helmholtz, Rayleigh-Taylor, thermal, and magneto-rotational instabilities, among others. Here we review the theory of some classic fluid instabilities that are present in PIP and highlight the unique effects introduced by partial ionization. {\bf The main emphasis of the review is put on instabilities in the partially ionized solar atmospheric plasma, although other astrophysical applications are also mentioned}. We focus on the mathematical and theoretical investigation of the onset and exponential growth of the instabilities. Results of the nonlinear evolution obtained from full numerical simulations are also discussed.